ANALISIS KEMIRINGAN DASAR SALURAN PADA SALURAN TERSIER DAERAH IRIGASI DONGGALA KODI - Setiyawan, Setiyawan; Affandy, Erwin; Anzar, Lisa Arnita (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2017)
As the plantation area, Donggala Kodi with mountainous topography made this region becomes an obstacle for farming people in which the function of the channel to deliver water from the river to the plantation area is not properly functioned. Tertiary channel of Donggala Kodi will highly possible to experience scour or erosion at the base of the channel, due to the large angle of the channel bottom slope so that the water velocity in the channelÂ  increased. This study aims to determine the performance of tertiary channel of Donggala Kodi. The research process begins with the collection of data which is then analyzed to evaluate the performance of tertiary channel. Donggala Kodi tertiary channel are using channel masonry 4,82 m/s, 5,49 m/s, 5,69 m/s, 5,61 m/s, 0,89 m/s, 5,03 m/s, 2,98 m/s, 3,76 m/s that its requirement maximum speed is 2.00 m/s and the minimum speed is 0.25 m/s. So it can be seen that the flow rate of the tertiary irrigation channel of Donggala Kodi do not meet the standards set by Standard Guidelines forÂ  Irrigation Planning Criteria Planning Section Channel KP-03, 2013.